Use of english fairy tales to teach listening comprehension skills among second grade students at República de Francia Elementary School, David, Chiriquí - Serrano, Isamar; Orocú, Yensy; Candanedo, Wilmo; Sleiman, Jihad (David, Panamá : UDELAS, 2013)
Literature plays an important role in our life. Fairy tales as a part of the children's literature coud be a valuable source for teaching listening and comprehension english in the foreing language. Fairy tales might be considered one of the possible supplementary teaching materials for english language learners.
TABLE OF CONTENTS CHART INDEX GRAPHIC INDEX INTRODUCTION CHAPTER I: USE OF ENGLISH FAIRY TALES TO TEACH LISTENING COMPREHENSION SKILLS CHAPTER II: THEORETICAL FRAMEWORK 2.1. Use of fairy tales to teach english 2.1.1. What fairy tales are 2.1.2. How english fairy tales have been use to teach english 2.1.3. Using fairy tales in the language classroom with young learners 2.2. The importance of listening input to enhance listening comprehension skills 2.3. Listening comprehension 2.3.1. Teaching listening comprehension skills 2.3.2. ESL methodology and listening comprehension 2.3.3. Listening comprehension and teaching english to children 2.4. Listening comprehension and fairy tales 2.5. Influence of motivation when teaching listening comprehension CHAPTER III: METHODOLOGICAL FRAMEWORK CHPTER IV: ANALYSIS AND RESULTS CONCLUSIONS RECOMMENDATIONS BIBLIOGRAPHY ANNEX
Incluye Table of contents
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA -- TEACHING; FACULTAD DE EDUCACIÓN SOCIAL Y ESPECIAL; ESCUELA DE EDUCACIÓN SOCIAl; LICENCIATURA EN DOCENCIA EN INGLÉS; ENGLISH FAIRY TALES; REPÚBLICA DE FRANCIA ELEMENTARY SCHOOL - CHIRIQUÍ; LISTENING COMPREHENSION